POLYMORPHISM AND EXPRESSION OF TLR2 GENE IN IRAQI PULMONARY TUBERCULOSIS PATIENTS - Lara Ghali A.Ali; Nawal Mohammed Utba; Ahmed Asmer Mankhi (Journal of Global Pharma Technology, 2018)
AbstractObjective The innate immune system has evolved as the first line of defense against microorganisms, which involves specific pathogen recognition receptors such as toll-like receptors (TLR). The aim of the present study was to investigate whether the TLR2 gene polymorphism could influence the susceptibility to pulmonary tuberculosis (TB) and its expression level as well as its concentration in patients’ sera.Methods A total of 120 subjects, including 80 patients with TB including 40 multiple drug resistance (MDR), 20 recently diagnosed (RD) and 20 old cases (OC) of TB patients, in addition to 40 healthy control, were examined for TLR2 polymorphism over locus -100 microsatellite guanine-thymine repeats, 24969 (T>C) and 5305 (C>T). TLR2 gene expression was assayed using a real time PCR technique; furthermore, sera from 68 TB patients and 20 healthy control were assayed for TLR2 level using ELISA technique.Results We found that the TC genotypes showed a significantly increased frequency in MDR patients than control (35% vs.12.5%, respectively; **P = 0.034), and the associated OR value 3.77 with EF value of 0.25. That may regard TLR-2 rs3804100 TC as TB susceptibility genotype in the investigated Iraqi patients. Whereas the TLR-2 serum levels varied significantly (*p<0.05) between studied groups in regard to TT genotypes. For TLR-2 rs7696323, all TB patients and control groups have CC genotypes (Wild type). In respect to (GT)n microsatellite repeat; GT repeat alleles had insignificant differences (p > 0.05) between MDR and OC than control groups, while RD group was significantly higher [**P = 0.006] than control group in GT(24) repeat allele, with OR value of 5.2 and EF value of 0.33. Furthermore, this GT repeat allele associated with susceptibility to TB. For TLR-2 gene expression, the results revealed a significant decrease (*p< 0.05) in TB patients in comparison to control groups. A novel TLR-2 rs3804100 SNPs were detected in Iraqi Arabs at g.24870 in 15%, g.24864 in 1.25% and g.25212 in 32.5% of patients. Nevertheless, in control the novel SNPs were g.24887 in 2.5%, g.25212 in 7.5% and g. 25216 in 7.5%. On the other hand, a novel TLR-2 rs7696323 SNPs were determined in Iraq Arabs patients and control at g.23934 in 10%, g.23564 in 1.25%, g.23460 in 6.25%, g.23445 in 11.25%, g. 23452 in 10% and g. 23477 in 10% of TB patients. While in control group, g.23957 in 7.5%, g.23438 in 7.5%, g.23445 in 7.5%, g.23452 in 32.5% and g.23443 in 2.5% of control.ConclusionTLR2 genetic polymorphisms influence susceptibility to pulmonary TB. TLR2 variants play a role in the development of TB disease, probably by affecting TLR2 expression level. Moreover, the present study showed that during anti-tuberculosis treatment, which were seems likely responsible for controlling infection and excess inflammation